Comparative study for sorption of arsenic on peanut shell biochar and modified peanut shell biochar. (May 2023) - Kushwaha, Rohit; Singh, Ram Sharan; Mohan, Devendra
Graphical abstract: Highlights: Peanut shell biochar (PSB) and modified PSB (MPSB) was used to remove arsenic. MPSB had higher efficiency 86% [As(III) @ pH 6] and 91.26% [As(V) @ pH 6] than PSB. Maximum adsorption capacity was 1.83 mg/g [As(V)] and 1.76 mg/g [As(III)] for PSB. Maximum adsorption capacity was 1.92 mg/g [As(V)] and 1.88 mg/g [As(III)] for MPSB. Freundlich isotherm and Pseudo-second order was a better fit for As(III) and As(V). Abstract: In this study, arsenite [As(III)] and arsenate [As(V)] removal efficiency of peanut shell biochar (PSB) and modified peanut shell biochar (MPSB) was compared in aqueous solutions. The modification was carried out with KMnO4 and KOH. Sorption efficiency of MPSB was relatively higher than PSB at pH 6 for As(III) (86%) and for As(V) (91.26%) for initial concentration of 1 mg/L, adsorbent dose of 0.5 g/L and 240 min equilibrium time at 100 rpm. Freundlich isotherm and pseudo-second order kinetic model suggested possible multilayer chemisorption. Fourier transform infrared spectroscopy showed that –OH, C–C, CC and C–O–C groups contributed significantly in adsorption for both PSB and MPSB. Thermodynamic study showed that the adsorption process was spontaneous and endothermic. Regeneration studies revealed that PSB and MPSB can be successfully used for three cycles. This study established that peanut shell is a low-cost, environment friendly and efficient biochar for removal of arsenic from water.